Establishment of Efficient Method for Evaluation of Heat Stress Tolerance of Herbaceous Plant Species and Selection of Heat-Tolerant Plants - Dong-Jin Park; Do-Hyun Kim; Seong-Hyeon Yong; Seon-A Kim; Kwan-Been Park; Seung-A Cha; Ji-Hyun Lee; Myung-Suk Choi (Horticulturae)
Due to climate change, heat-tolerant species have become increasingly important; however, the selection system for herbaceous plants has yet to be well established. This study aimed to establish a selection system for heat-tolerant plant species and to identify such species. Heat stress at 50 °C for 120 min was applied to 27 plant species using a heat treatment and recovery model. Among them, four herbaceous species—Hemerocallis fulva, Heliopsis longipes, Hosta plantagines, and Scilla scilloides—were selected by measuring their electrolyte leakage index (ELI). Additionally, species with high ELI values (Centaurea cyanus) and low ELI values (S. scilloide) were selected to determine the optimal temperature and time for the heat treatment using linear regression analysis. The selected heat-tolerant herbaceous plants survived under optimal heat stress conditions (120 min at 50 °C). The degree of cell death in the selected plant species was measured using Evans blue staining. The results showed that the cell death indexes of heat-tolerant species were less than 22% after heat treatment, compared to over 57% in heat-sensitive species. Furthermore, the recovery ability at room temperature after heat treatment was assessed using the DAB staining method. The selected heat-tolerant plant species recovered quickly (within 90 min), whereas the heat-sensitive species required over 480 min for recovery. The analytical method developed in this study can more accurately determine the response of various plants to heat stress and has high reproducibility. Therefore, it is considered an excellent method for establishing a heat-tolerant plant selection system.